Evaluating The Levels of Cadmium, Lead and Nickel Present In Solanum Tuberosum, L. (Irish Potato) Marketed In Industrialized Areas of Ogun State, Nigeria. - Olabanji, Daodu John; Oluwafeola, Towolawi; Saka, Kasim Lateef; Ebunoluwa, Adejumo Olufunmilayo; James, Olaitan Olatunde; Babasola, Fagbohun Ayodele; Friday, Ibitoye Samuel; Adekunle, Ayodele Olatunde (Nigerian Journal of Pharmaceutical and Applied Science Research, 2020)
Solanum tuberosum, L. (Irish potato), the world’s fourth largest food crop and a staple in many diets around the world is a source of highly digestible carbohydrate and nutritionally complete protein, as well as being an excellent source of other essential nutrients. The incidence of heavy metals contamination in humans through food, water, air or skin absorption, in varying levels of concentration has been reported. This study was carried out to determine the levels of three heavy metals (cadmium Cd, Nickel Ni, and lead Pb) in Solanum tuberosum around industrialized areas. Samples were purchased from markets at Sagamu, Ogijo and Sango- Ota industrialized areas of Ogun state. Tissue and peeled samples were pre-treated using acid digestion and the concentrations of Ni, Pb and Cd were determined using Atomic Absorption Spectrophotometer (AAS)(Perkin Elmer A. Analyst 200 Germany). The concentrations of the three heavy metals in all the tissue samples, except for Pb, in the Sango-Ota tissue samples, were within the standard permissible limit set by the WHO/FAO. However, the concentration of the heavy metals in all the peel samples exceeded the permissible limits, and the Sango-Ota peels have the highest concentrations while Sagamu peels were the lowest. The presence and concentration of industries have significant consequence on the levels of heavy metals presence in potato which may constitute great threat to safety and health of the consumers.